Ekonomi ceria / Aizat Syafiq Asmadi - Asmadi, Aizat Syafiq (2022)
Ekonomi Ceria is a driving institution that is located in Temerloh, Pahang. This institution is a place where people can get various of driving license, motorcycles driver's license and more with a variety affordable price. this institution is also equipped with a complete driving circuits so the driver can practice driving various vehicle such as car, lorry and motorcycle until they became more proficient. the reason i choose to rebrand and redesign this situation is because this institution does not have a clear corporate identity.